Estimation of Repaglinide and Metformin HCls from Pharmaceutical Formulation by Q-Absorbance Ratio Method Using UV Spectrophotometer - Dr. Khagga. Bhavyasri; Samreen Begum; D. Suchitra; V. Narmada; Dr. Mogilli. Sumakanth (International Journal of Pharma and Bio Sciences, 2024)
Both drugs are combined for people with high blood sugar levels and cannot be treated by a single medication. The main aim of this study is to determine Repaglinide and Metformin HCl in bulk simultaneously and combined dosage form using the Q-Absorbance ratio method with a UV-Visible spectrophotometer as per United States Pharmacopoeia. The solvent used was distilled water and Acetonitrile for Metformine and Repaglinide.Theλmax of Metformin and Repaglinide showed at 232nm and 244nm, respectively. Quantifying Metformin and Repaglinide in a Combined dosage form was done using ACN: water (70:30%v/v). The isosbestic point was found at 245.5nm. All the parameters were validated according to ICHQ2(R1) guidelines. All the parameters were found to be within the limits. Therefore, it was observed that the Q-absorption approach could be used to estimate Repaglinide and Metformin HCl simultaneously.